2017
DOI: 10.5688/ajpe81115
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Curbside Consults to Develop Team Communication and Improve Student Achievement of Learning Outcomes

Abstract: Objective. To design and implement a series of activities focused on developing interprofessional communication skills and to assess the impact of the activities on students' attitudes and achievement of educational goals. Design. Prior to the first pharmacy practice skills laboratory session, pharmacy students listened to a classroom lecture about team communication and viewed short videos describing the roles, responsibilities, and usual work environments of four types of health care professionals. In each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…It is stated that IPE facilitates the students to improve interprofessional communication skills. 23 After the implementation of IPE, students gained a strong confidence in communication with other professions. 24 Furthermore, the participants stated that collaboration skill will increase by implementing the program.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that IPE facilitates the students to improve interprofessional communication skills. 23 After the implementation of IPE, students gained a strong confidence in communication with other professions. 24 Furthermore, the participants stated that collaboration skill will increase by implementing the program.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different instruments were applied to collect information on students’ outcomes, such as skills checklists, in-depth interviews, agreement level on Likert scales for different constructs (i.e., tools on self-perceived knowledge, attitudes, communication, interprofessional practice, interdisciplinary education or confidence), or multiple-choice examinations. Contrary to what would be desirable, only some studies have applied pre- and post-surveys, and the number of studies enrolling multiple evaluations was also limited [5,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. On the one hand, all of these limitations compromise the accuracy and representativeness of the present study findings and conclusions; on the other hand, this clearly shows the need to improve the robustness of learning outcome evaluations in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, a training/video session or a lecture was provided before the initial laboratory sessions, thus improving students’ prior knowledge. Active-learning strategies successively enhanced students’ self-confidence, identification of drug-related problems, patient management or communication skills [43,45,46,47]. The use of virtual reality and avatars is advancing [55] and has been tested in Portuguese pharmacy undergraduate programs with promising results [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of these referred to (inter)national IP competency frameworks (see Table 3). Some publications reported a mix of different competency frameworks, for example Kirwin et al (2017) who used a combination of IP and profession specific competencies, namely the IPEC Core Competencies for Interprofessional Education and Collaborative Practice and the Centre for Advancement of Pharmacy Education competencies. Thirteen publications described competency domains instead of a framework; for example, Garbee et al (2013) reported team performance, existing of communication, role clarity, and situational awareness as IP competency domains.…”
Section: Performancesmentioning
confidence: 99%